RASIONALITAS PENGGUNAAN ANTIBIOTIK PADA PASIEN INFEKSI SALURAN KEMIH (ISK) DI INSTALASI RAWAT INAP RSUD UNDATA PALU TAHUN 2012 - Febrianto, Aldu Wijaya; Mukaddas, Alwiyah; Faustine, Inggrid (Univ. Tadulako, 2013)
ABSTRACT Urinary Tract Infection (UTI) is a bacterial infection of urinary tract that antibiotic was the first step on therapy. Antibiotic usage at hospitalized patients in developing country is 30-80%, but from all of that 20-65% antibiotic usage was considered inappropriate. It can raise resistance symptoms. This research is aimed to find out the rational of antibiotics usage including right indication, drug, dosage, frequency and duration in UTI patients. This research was descriptive research which was done retrospectively by looking at medical records of UTI patients, in order to explain or to illustrate the characteristics of each of the variables on this study including: patient characteristics, clinical characteristics and rationality of drug usage. The outcome of this study were as follow: Rationality treatment was 96.5 % in precise indications, right drug was 66.7%, right dosage was 53%, right frequency of antibiotic was 53%, and appropriate duration of antibiotic usage was 49.4 % . The use of antibiotic on UTI patients at Undata Palu Hospital in 2012, it could not be clasified as rational use yet.